Pengembangan Media Pembelajaran Matematika Interaktif Berbasis Articulate Storyline untuk Memfasilitasi Kemandirian Belajar Siswa pada Materi Transformasi Geometri Kelas IX SMP/MTs - Armi Parlusi Putri; Susda Heleni; Atma Murni (Mathematics Education Study Program, 2022)
This research is a development research (R&D) with the aim of producing an interactive mathematics learning media based on Articulate Storyline that meets the valid and practical requirements to assist grade IX students of SMP/MTs in understanding geometry transformation material and facilitating student learning independence. This development research uses the Borg and Gall development model which consists of ten stages, but in this study only reached stage seven, namely: (1) potential and problems; (2) data collection; (3) product design; (4) design validation; (5) design revision; (6) product trial; and (7) product revision. Researchers explore potentials and problems through interviews, observations, questionnaires, and literature studies. Learning media and guidebooks were validated by three validators. The instrument used was a learning media validation questionnaire and a learning media guide book validation questionnaire. The average value of learning media validation is 3.37 with a very valid category and the average value of guide book validation is 3.52 with a very valid category. The learning media was tested on six students of class IX SMP, the instruments used were student response questionnaires and student learning independence questionnaires. The product trial result was 0.96 with a very practical category and very well facilitated student learning independence of 84.33%.